Murine Model of Sinusitis Infection for Screening Antimicrobial and Immunomodulatory Therapies - Alford, Morgan A.; Choi, Ka-Yee G.; Trimble, Michael J.; Masoudi, Hamid; Kalsi, Pavneet; Pletzer, Daniel; Hancock, Robert E. W. (Frontiers in Cellular and Infection Microbiology, 2021)
The very common condition of sinusitis is characterized by persistent inflammation of the nasal cavity, which contributes to chronic rhinosinusitis and morbidity of cystic fibrosis patients. Colonization by opportunistic pathogens such as Staphylococcus aureus and Pseudomonas aeruginosa triggers inflammation that is exacerbated by defects in the innate immune response. Pathophysiological mechanisms underlying initial colonization of the sinuses are not well established. Despite their extensive use, current murine models of acute bacterial rhinosinusitis have not improved the understanding of early disease stages due to analytical limitations. In this study, a model is described that is technically simple, allows non-invasive tracking of bacterial infection, and screening of host-responses to infection and therapies. The model was modified to investigate longer-term infection and disease progression by using a less virulent, epidemic P. aeruginosa cystic fibrosis clinical isolate LESB65. Tracking of luminescent bacteria was possible after intranasal infections, which were sustained for up to 120-hours post-infection, without compromising the overall welfare of the host. Production of reactive oxidative species was associated with neutrophil localization to the site of infection in this model. Further, host-defence peptides administered by Respimat® inhaler or intranasal instillation reduced bacterial burden and impacted disease progression as well as cytokine responses associated with rhinosinusitis. Thus, future studies using this model will improve our understanding of rhinosinusitis etiology and early stage pathogenesis, and can be used to screen for the efficacy of emerging therapies pre-clinically.